The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1152/ajpendo.00275.2002
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin-deficient mice lose more skeletal muscle mass than wild-type controls during hindlimb suspension

Abstract: Myostatin inhibits myogenesis. Therefore, we sought to determine if mice lacking the myostatin gene [Mstn(-/-)] would lose less muscle mass than wild-type mice during 7 days of hindlimb suspension (HS). Male Mstn(-/-) and wild-type (C57) mice were subjected to HS or served as ground-based controls (n = 6/group). Wild-type mice lost 8% of body mass and approximately 13% of wet mass from biceps femoris, quadriceps femoris, and soleus, whereas the mass of extensor digitorum longus (EDL) was unchanged after HS. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 28 publications
(34 reference statements)
9
63
1
1
Order By: Relevance
“…It appears that mdx mice injected with myostatin antibodies for 3 mo showed an increase in muscle mass (11). Importantly, however, mice with muscle hypertrophy due to knockout of the myostatin gene show muscle atrophy that is equal to or greater than that on wild-type mice in response to unloading (68). This finding indicates that unloading-induced atrophy does not require myostatin.…”
Section: Myostatinmentioning
confidence: 96%
“…It appears that mdx mice injected with myostatin antibodies for 3 mo showed an increase in muscle mass (11). Importantly, however, mice with muscle hypertrophy due to knockout of the myostatin gene show muscle atrophy that is equal to or greater than that on wild-type mice in response to unloading (68). This finding indicates that unloading-induced atrophy does not require myostatin.…”
Section: Myostatinmentioning
confidence: 96%
“…38 Absence of myostatin expression in myostatin knockout mice did not prevent the loss of muscle mass after hindlimb suspension. On the contrary, these mice are more susceptible to unloading-induced skeletal muscle atrophy.…”
Section: Anabolic Activationmentioning
confidence: 99%
“…On the contrary, these mice are more susceptible to unloading-induced skeletal muscle atrophy. 38 In recent animal experiments, Heineke et al 39 showed that a heart-specific deletion of myostatin with an Nkx2.5-cre allele prevented skeletal muscle atrophy in heart failure. In consequence, they postulated that myocardial myostatin expression controls muscle atrophy in heart failure via elevated serum myostatin concentrations.…”
Section: Anabolic Activationmentioning
confidence: 99%
“…While it has been known for some time that the loss in muscle protein due to disuse results from decreases in protein synthesis and increases in protein degradation rates (2), we are just beginning to learn about the upstream triggers and signaling pathways that regulate the changes in these target systems that determine protein content. While myostatin (3,4) and glucocorticoids (5) have been studied for a role in atrophy, and both can induce atrophy in normal muscle, neither is required for disuse atrophy in vivo (5,6). Recent work suggests that inhibition of the Akt growth pathway in muscle may be involved in the progression of disuse atrophy.…”
Section: Introductionmentioning
confidence: 99%